1992
DOI: 10.1177/00220345920710120701
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age on Immunoglobulin Content and Volume of Human Labial Gland Saliva

Abstract: Stimulated lower labial (LLGF) and parotid salivary volumes and IgG, IgA, and IgM concentrations were measured in 264 subjects whose ages ranged from 17 to 76 years. A significant (p < 0.001) age-related decline in LLGF output was observed for subjects over this age range. Sixty-three percent of the subjects in the 18-20-year-old group (n = 46) secreted at least 10 microL of labial saliva in a 7-10-minute period, while approximately 70% of the subjects in the two oldest groups (61-70 and 71-76 years old) secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
2
3

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 24 publications
4
23
2
3
Order By: Relevance
“…The LGS flow rate values were also comparable with data published earlier [Smith et al, 1992;Ferguson, 1999]. During the test days the UWS and LGS flow rates did not differ signifi- Asterisks denote statistically significant differences from control (C) values: **pd0.02, ***p d0.01.…”
Section: Discussionsupporting
confidence: 86%
“…The LGS flow rate values were also comparable with data published earlier [Smith et al, 1992;Ferguson, 1999]. During the test days the UWS and LGS flow rates did not differ signifi- Asterisks denote statistically significant differences from control (C) values: **pd0.02, ***p d0.01.…”
Section: Discussionsupporting
confidence: 86%
“…Second, in contrast to the previous study that was conducted only on men, the present study included women and men. However, human epidemiological studies have failed to detect gender differences in sIgA~e.g., Smith, Joshipura, Kent, & Taubman, 1992!. Third, whereas Willemsen et al~1998!…”
Section: Beta-adrenergic Influences On Secretory Responses To Mentalmentioning
confidence: 97%
“…A decrease in salivary secretion rates with age has also been observed in stimulated parotid, 78 resting and stimulated submandibular 83 and resting 84,85 and stimulated 86,87 minor glands. On the other hand, an age-related decline was not observed in other studies of resting 87 and stimulated 88 whole salivary flow rate.…”
Section: Salivary Flow Ratesmentioning
confidence: 72%
“…In an early study, an age-related decline in IgA levels in nasal secretions of hospitalized patients with respiratory disease was described. 162 However, many subsequent investigations, which included healthier and older subjects, reported that total salivary IgA concentrations did not decline 86 or, more commonly, increased with age. 81,163,164 Other studies have demonstrated that salivary IgA secretion rates, regarded as a more accurate measurement of mucosal function, 165 declined with increased age in whole saliva of healthy individuals.…”
Section: Changes In Oral Host Defences With Agementioning
confidence: 99%